Sustainable Financial Systems: Integrating Indigenous Knowledge through Tanggung Renteng System in Setia Bhakti Wanita Consumer Cooperative - Meitry Adinda; Cupian Cupian; Siti Chaerani Djen Amar (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aimed to explore the Tanggung Renteng (Mutual Responsibility) system, a local wisdom-based institution, in the operational activities and fund management of the Setia Bhakti Wanita Consumer Cooperative to promote a sustainable financial system. This study used a qualitative method with a case study approach that analyzed data based on literature studies. The results of this study indicated that the operational activities and fund management of the Setia Bhakti Wanita Consumer Cooperative based on the Tanggung Renteng system could foster a financial sustainability system. It is contributive and inclusive, empowering members who pay attention to cultural, economic, and social-environmental aspects.